2017
DOI: 10.4088/jcp.15m10498
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Plus Antipsychotics Versus Placebo Plus Antipsychotics in Severely Ill Decompensated Postmenopausal Women With Schizophrenia or Schizoaffective Disorder

Abstract: ClinicalTrials.gov identifier: NCT01280305.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 2 publications
1
45
4
2
Order By: Relevance
“…We found that the administration of adjunctive raloxifene significantly improved memory and attention compared to placebo, which is consistent with the findings of an earlier trial showing significant improvement in frontal cortex‐dependent memory and executive function with adjunctive raloxifene therapy in postmenopausal women with schizophrenia . Conversely, in a recent randomised‐controlled trial of 200 severely ill and decompensated postmenopausal women, raloxifene showed no significant cognitive benefit or symptom severity reduction as an adjunctive treatment compared to placebo (although the ability to detect cognitive improvement may have been limited by the extensive symptom severity in the sample). Overall, despite inconsistencies as to which specific clinical aspects of schizophrenia are ameliorated by raloxifene, it is clear that the SERM has potential as an adjunctive medication in the treatment of schizophrenia.…”
Section: Evidence That Sex Steroid Manipulations Can Be Useful Adjuncsupporting
confidence: 88%
“…We found that the administration of adjunctive raloxifene significantly improved memory and attention compared to placebo, which is consistent with the findings of an earlier trial showing significant improvement in frontal cortex‐dependent memory and executive function with adjunctive raloxifene therapy in postmenopausal women with schizophrenia . Conversely, in a recent randomised‐controlled trial of 200 severely ill and decompensated postmenopausal women, raloxifene showed no significant cognitive benefit or symptom severity reduction as an adjunctive treatment compared to placebo (although the ability to detect cognitive improvement may have been limited by the extensive symptom severity in the sample). Overall, despite inconsistencies as to which specific clinical aspects of schizophrenia are ameliorated by raloxifene, it is clear that the SERM has potential as an adjunctive medication in the treatment of schizophrenia.…”
Section: Evidence That Sex Steroid Manipulations Can Be Useful Adjuncsupporting
confidence: 88%
“…Raloxifene was well tolerated and offers potential for its use in this difficult to treat patient cohort and follows on previous trials from the same centre showing an effect of adjunctive oestradiol 200mcg in symptom improvement, particularly positive symptoms (Kulkarni et al, 2015). However, other studies have failed to find a benefit for adjunctive raloxifene in improving cognitive symptoms in non-TR schizophrenia (Kulkarni et al, 2016, Weiser et al, 2017, or in improving symptom severity (Weiser et al, 2017).…”
Section: Alternatives To Clozapine In Trsmentioning
confidence: 59%
“…In perimenopausal and postmenopausal women (aged 40–70 years) with treatment‐resistant schizophrenia, raloxifene reduced symptom severity and improved likelihood of clinical response (Kulkarni et al, ). By contrast, another study found that severely ill, postmenopausal women with schizophrenia receiving adjunct raloxifene did not show symptom improvement and in fact experienced worsened positive and negative symptoms (Weiser et al, ). The authors concluded that while raloxifene may be beneficial for some patients, further research is needed to identify suitable subgroups for safe administration.…”
Section: Are Gonadal Steroid Hormones the Mediating Factor?mentioning
confidence: 96%